2017
DOI: 10.1080/15384101.2017.1339850
|View full text |Cite
|
Sign up to set email alerts
|

Murine mesenchymal cells that express elevated levels of the CDK inhibitor p16(Ink4a)in vivoare not necessarily senescent

Abstract: Age-related health decline has been attributed to the accumulation of senescent cells recognized in vivo by p16(Ink4a) expression. The pharmacological elimination of p16(Ink4a)-positive cells from the tissues of mice was shown to extend a healthy lifespan. Here, we describe a population of mesenchymal cells isolated from mice that are highly p16(INK4a)-positive are proficient in proliferation but lack other properties of cellular senescence. These data, along with earlier reports on p16(Ink4a)-positive macroph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 20 publications
0
23
0
Order By: Relevance
“…While SA-β-gal is widely used as a marker of cellular senescence, [20][21][22] its elevated activity can be found in some other cells such as activated macrophages. 48,55 These SA-β-gal-positive macrophages can be harmful and have been found to accumulate in injured and aged tissues contributing to chronic inflammation. 44,45 Importantly, we have shown that SSK1 decreases the number of SA-β-gal-positive macrophages in injured lungs and aged livers (Supplementary information, Fig.…”
Section: Discussionmentioning
confidence: 99%
“…While SA-β-gal is widely used as a marker of cellular senescence, [20][21][22] its elevated activity can be found in some other cells such as activated macrophages. 48,55 These SA-β-gal-positive macrophages can be harmful and have been found to accumulate in injured and aged tissues contributing to chronic inflammation. 44,45 Importantly, we have shown that SSK1 decreases the number of SA-β-gal-positive macrophages in injured lungs and aged livers (Supplementary information, Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Senescent cells can have increased lysosomal b-galactosidase activity (senescence-associated b-galactosidase [SA-b-gal]), but so can macrophages and other cell types [57,58]. Some, but not all senescent cells may have high expression of p16 INK4a , but p16 INK4a expression can be high in activated macrophages and many other cell types [59]. Like p16 INK4a , p21 CIP1 is not fully sensitive or specific for detecting senescent cells [60].…”
Section: Cellular Senescencementioning
confidence: 99%
“…D + Q does not kill the activated macrophages that can accumulate in adipose tissue in diabetes [51]. These macrophages have increased p16 INK4a expression but are not senescent [59]. Consistent with this, senolytic drugs also do not target atherosclerotic foam cells, which are essentially activated macrophages, as opposed to the truly senescent cells that are deeper within plaques or the media of atherosclerotic blood vessels that are ablated by D + Q [113].…”
Section: Senolytics Alleviate Multiple Disorders In Experimental Animalsmentioning
confidence: 99%
“…A study by Hall and colleagues reported that macrophages express p16 Ink4a and SA-β-Gal as part of a reversible response to physiological immune stimuli rather than through senescence, indicating a senescence-independent increase of p16 Ink4a -expression [120]. Moreover, proliferating mesenchymal cells of young mice lacking other properties of cellular senescence were found to be highly positive for p16 Ink4a [121]. In line with these findings, we observed significant expression of p16 Ink4a both in microglia from newborn and young adult murine brains [122].…”
Section: Markers Of Aging and Senescencementioning
confidence: 99%